1975
DOI: 10.3758/bf03204091
|View full text |Cite
|
Sign up to set email alerts
|

The relation between size and apparent heaviness

Abstract: A formula for the size-weight illusion was derived from the Stevens and Rubin (1970) finding that heaviness functions form a family of power functions that converge at a common point in the vicinity of the heaviest weight that can be lifted. Magnitude estimations of the apparent heaviness of 42 plastic cylinders varying in size and weight were obtained from 20 subjects, who were allowed to use both hands to lift the weights. It was predicted that this would increase the maximum weight that could be lifted, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 24 publications
10
65
1
1
Order By: Relevance
“…Stevens and Rubin (1970) and Cross and Rotkin (1975) suggested that perceived heaviness is dependent on object volume (i.e., percept-percept coupling), indicating perceptual dependence of touch perception on visual perception (Epstein, 1982). However, Amazeen (1999) and Riley and Turvey (2001) found that visual and touch influences were additive, suggesting perceptual independence (see also Grandy & Westwood, 2006).…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stevens and Rubin (1970) and Cross and Rotkin (1975) suggested that perceived heaviness is dependent on object volume (i.e., percept-percept coupling), indicating perceptual dependence of touch perception on visual perception (Epstein, 1982). However, Amazeen (1999) and Riley and Turvey (2001) found that visual and touch influences were additive, suggesting perceptual independence (see also Grandy & Westwood, 2006).…”
Section: Methods Participantsmentioning
confidence: 99%
“…A classic illustration is the size-weight (S-W) illusion (see, e.g., Charpentier, 1891;Cross & Rotkin, 1975;Stevens & Rubin, 1970). When confronted with two objects of the same mass but different size, people typically report that the larger object is lighter than the smaller object.…”
mentioning
confidence: 99%
“…I discuss the nature of this illusion briefly; a more detailed account is given in Jones's (1986) More recent studies of the size-weight illusion show that when the volume of an object remains constant, its heaviness increases as a power function of weight (Harper & Stevens, 1948) but that at different constant volumes, a family of power functions is required to describe the relation between weight and heaviness (Cross &Rotkin, 1975;Stevens&Rubin, 1970). Various mathematical expressions, ranging from logarithmic (Stevens & Rubin, 1970) to exponential decay functions (Rule & Curtis, 1977), have been proposed to describe the relation between heaviness and volume as a function of weight.…”
Section: Size-weight Illusionsmentioning
confidence: 99%
“…Models positing a role for topdown processing in heaviness perception (Ross, 1969; Ellis & Lederman, 1998 or 'antiBayesian' biases (Brayanov & Smith, 2010) have been explored. Likewise, a number of early models claimed to describe especially the SWI (which is more robust and larger in magnitude than the MWI) in a cue combination framework by arbitrarily placing a negative weight on the expectancy cue (Anderson, 1970) or other similar assumptions (Cross & Rotkin, 1975) . Many of these models were unsatisfactory primarily because they described the magnitude of weight illusions but did not explain why they occurred.…”
Section: Discussionmentioning
confidence: 99%